2010
DOI: 10.1111/j.1365-2796.2010.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Combined analyses and extended follow‐up of two randomized controlled homocysteine‐lowering B‐vitamin trials

Abstract: Abstract. Ebbing M.,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
38
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(43 citation statements)
references
References 45 publications
4
38
1
Order By: Relevance
“…23 Moderately increased plasma levels of Hcy and genetic factors associated with enzymatic abnormalities of folic acid and Hcy metabolism play an important role in the development of CVD. 24,25 Most studies that reported higher Hcy levels in bipolar patients were carried out during euthymia and focused on functional and cognitive deterioration. [26][27][28] To our knowledge, this is the first study to assess Hcy levels in the same patients in both states, mania and euthymia; it is also the first study to attempt to correlate Hcy with markers of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…23 Moderately increased plasma levels of Hcy and genetic factors associated with enzymatic abnormalities of folic acid and Hcy metabolism play an important role in the development of CVD. 24,25 Most studies that reported higher Hcy levels in bipolar patients were carried out during euthymia and focused on functional and cognitive deterioration. [26][27][28] To our knowledge, this is the first study to assess Hcy levels in the same patients in both states, mania and euthymia; it is also the first study to attempt to correlate Hcy with markers of CVD.…”
Section: Discussionmentioning
confidence: 99%
“…364 Beneficial effects ascribed to anti-oxidants were based on 365 epidemiological as well as in-vitro studies. However, when tested 366 in large scale RCTs, little or no effects have been found [56]; or 367 perhaps even harm as for beta-carotene with an increased lung 368 cancer risk [57] and for folic acid plus vitamin B12 an increased 369 cancer and all-cause mortality risk [58]. We should therefore take …”
Section: Introductionmentioning
confidence: 97%
“…A recent analysis suggests that cardiovascular risk prediction by tHcy is confined to the Hcy fraction that does not respond to B-vitamins. 89 There are mechanisms that are "resistant" to Hcy-lowering action of folic acid. For example, elevated tHcy can result in production of autoantibodies directed against N-Hcy-protein adducts, 86 that tend to remain increased despite reduction in tHcy.…”
Section: Undas and Ariëns Fibrin Clot Properties And Thrombosis E91mentioning
confidence: 99%